2018
DOI: 10.1080/02660830.2018.1523102
|View full text |Cite
|
Sign up to set email alerts
|

Being in constant transition or recurrent formation: Non-traditional graduates’ life transitions before, during and after higher education in Sweden

Abstract: The aim of this article is to examine non-traditional graduates' life transitions before, during, and after higher education (HE) in Sweden. The article builds on a theory called biographical work, which is used for understanding non-traditional graduates' identity formation and transformation. The article is based on the narratives of two non-traditional graduates who were selected from biographical interviews with nine non-traditional graduates, 2-5 years after graduation from HE. By exploring significant ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Finally, we conducted a synchronic analysis, where we compared their stories of participation in different CoPs with the fieldwork in the mill town. Using both synchronic and diachronic analyses helped to understand the participation in the local community, as well as their biographical processes when they tried to integrate their situated belonging with their biographies (Bron andThunborg 2017, Thunborg andBron 2019).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we conducted a synchronic analysis, where we compared their stories of participation in different CoPs with the fieldwork in the mill town. Using both synchronic and diachronic analyses helped to understand the participation in the local community, as well as their biographical processes when they tried to integrate their situated belonging with their biographies (Bron andThunborg 2017, Thunborg andBron 2019).…”
Section: Methodsmentioning
confidence: 99%
“…We also stress that learning to belong is part of identity formation. We define identity as how people see and present themselves in relationships, and regarding others (Thunborg and Bron 2019).…”
Section: Previous Research About Asylum Seekers Learning To Belongmentioning
confidence: 99%
“…We found that, in the interpretations of our respondents, graduating effaces any previous drop out. As Thunborg and Bron (2019) put it, "being in recurrent formation means returning to well-known paths in life and learning reactively by reflecting on experiences" (p. 36). Our findings confirm the secure feelings these students had when they decided to enroll for another university degree.…”
Section: Discussionmentioning
confidence: 99%
“…At the upper secondary level, the legal right is restricted to courses that give eligibility for higher education or higher vocational education, as part of a policy to widen access for 'nontraditional' students (cf. Thunborg and Bron 2019). In addition to these courses, the municipality should also strive to offer other upper secondary level courses, including vocational education, corresponding to needs and demands.…”
Section: Aim and Research Questionsmentioning
confidence: 99%